Nine new species of Soesilarishius from Brazil (Araneae: Salticidae: Euophryinae) - Ruiz, Gustavo Rodrigo Sanches (Zootaxa, 2013)
Nine new species of Soesilarishius Makhan, 2007 are described from Brazil, raising the genus member list up to 20 spe-cies. Soesilarishius chaplini sp. nov., S. paxiuba sp. nov. and S. muiratinga sp. nov. are described from the state of Pará. Soesilarishius bicrescens sp. nov., S. excentricus sp. nov. and S. flagellator sp. nov. are described from the state of Piauí. Soesilarishius macrochelis sp. nov. and S. cearensis sp. nov. are described from the state of Ceará. Soesilarishius taber-narius sp. nov. is described from the state of Bahia. Both sexes are described for the new species, except for S. muiratinga, S. bicrescens, S. excentricus and S. tabernarius, whose females remain unknown.